Maternal traditional dietary pattern and antiretroviral treatment exposure are associated with neonatal size and adiposity in urban, black South Africans - Wrottesley, SV; Ong, KK; Pisa, PT; Norris, SA (Cambridge University Press, 2018)
© 2018 The Authors. This study examines the associations between maternal Traditional dietary pattern adherence and HIV/treatment with neonatal size and adiposity in urban, black South Africans, as well as how specific maternal factors-that is BMI and gestational weight gain (GWG)-may influence these associations. Multiple linear regression models were used to examine associations among maternal Traditional diet pattern adherence (pattern score), HIV/treatment status (three groups: HIV negative, HIV positive (antenatal antiretroviral treatment (ART) initiation), HIV positive (pre-pregnancy ART initiation)), BMI and GWG (kg/week), and newborn (1) weight:length ratio (WLR, kg/m) in 393 mother-neonate pairs, and (2) Peapod estimated fat mass index (FMI, kg/m3) in a 171-pair subsample. In fully adjusted models, maternal obesity and GWG were associated with 0·25 kg/m (P=0·008) and 0·48 kg/m (P=0·002) higher newborn WLR, whereas Traditional diet pattern score was associated with lower newborn WLR (-0·04 kg/m per +1 sd; P=0·033). In addition, Traditional diet pattern score was associated with 0·13 kg/m3(P=0·027) and 0·32 kg/m3(P=0·005) lower FMI in the total sample and in newborns of normal-weight women, respectively. HIV-positive (pre-pregnancy ART) v. HIV-negative (ref) status was associated with 1·11 kg/m3(P=0·002) higher newborn FMI. Promotion of a Traditional dietary pattern, alongside a healthy maternal pre-conception weight, in South African women may reduce newborn adiposity and metabolic risk profiles. In HIV-positive women, targeted monitoring and management strategies are necessary to limit treatment-associated effects on in utero fat deposition.
Keywords: ADP air displacement plethysmography; ART antiretroviral treatment; DXA dual-energy X-ray absorptiometry; FMI fat mass index; GWG gestational weight gain; QFFQ quantitative FFQ; WLR weight:length ratio; Antiretroviral treatment; Neonatal adiposity; Pregnancy; South Africa; Traditional dietary patterns; Adiposity; Adult; Anti-Retroviral Agents; Birth Weight; Black People; Body Composition; Body Height; Culture; Diet; Female; HIV Infections; Humans; Infant, Newborn; Male; Maternal Nutritional Physiological Phenomena; Mothers; Obesity; Preconception Care; Pregnancy; Pregnancy Complications, Infectious; Prenatal Care; South Africa; Urban Population; Weight Gain